Pengaruh Pendapatan Asli Daerah dan Laju Inflasi terhadap Produk Domestik Regional Bruto tahun 1998 – 2008 Menggunakan Program Minitab 14 - Afiyah, Siti Nurul (LP2M Institut Teknologi dan Bisnis ASIA Malang, 2011)
Economic problems that hit Indonesia and the trust can provide positive and negative impacts of efforts to improve the welfare of the people of Indonesia. Due to the economic crisis and experienced trust has paved the way for the emergence of a total reform in all aspects of life of the nation of Indonesia. One element of reform is the requirement of granting total autonomy to the regions and city districts. In connection with the inflation that occurred in Indonesia in particular the city of Malang, the inflation impact on Gross Regional Domestic Product indirectly through the amount of the prices of goods in society. This study focused on how the influence of local revenue and the rate of inflation to the Gross Regional Domestic Product during the period 1998 to 2008. Revenue have a significant effect on the city's Gross Regional Domestic Product is equal to 66.5% of Malang, while the other independent variables are not significantly affect the rate of inflation this is due to the inflation rate does not directly influence.